Hydrothermal Synthesis of Zinc-Incorporated Nano-Cluster Structure on Titanium Surface to Promote Osteogenic Differentiation of Osteoblasts and hMSCs - Tang, Ze-hua; Su, Shan; Liu, Yao; Zhu, Wen-qing; Zhang, Song-mei; Qiu, Jing (Frontiers in Materials, 2021)
In this study, a novel modification strategy was established to synthesize a zinc-incorporated nano-cluster structure on titanium surface in a two-step hydrothermal reaction, and the osteogenic differentiation of osteoblasts and human bone marrow mesenchymal cells (hMSCs) was studied in the presence of this synthesized nanostructure. Analyses of the surface topography and elemental composition revealed that the zinc-containing cluster-like nanostructure was successfully prepared on the titanium surface. By altering the reaction time, three surface modifications were established. The three modified titanium surfaces had improved hydrophilicity and could continuously release zinc ions in a controlled manner. In vitro study displayed that three modified titanium surfaces, especially the samples prepared by reacting for 15 min, exhibited enhanced cell adhesion, proliferation, and osteogenic differentiation compared to the pure titanium surface. The study therefore conclude that the zinc-incorporated nano-cluster modification of titanium surface through a simple procedure can establish an enhanced osteogenic microenvironment and exhibit a potential strategy of titanium surface modification to accelerate the dental implant osseointegration.